An occupancy grid ruler based highly robust displacement measurement method and its application in brake wear assessment. (December 2022) - Luo, Yang; Shi, Jianghai; Wei, Jiang; Cao, Hongrui; Lan, Hai
Highlights: This article presents a novel displacement measurement method based on occupancy grid ruler(OGR). The OGR achieves outliers screening and waveform smoothing of the measurement values sequences. The OGR is enhanced by observation time windows and specially-designed updating functions. The OGR can be promoted in the scenarios of quasi-static measurement with specified resolution. Abstract: The displacement of a multi-plate brake actuator provides insights into degradation. However, the displacement signal in a low sampling frequency is difficult to be assessed due to noise and outliers. This paper proposes an occupancy grid ruler (OGR) based displacement measurement method that sequentially implements displacement signal denoising and measurement value outlier removal and smoothing. The displacement and duration measurement values are extracted from the signal denoised by generalized Moreau envelope total variation. Next, the measurement values are assessed by the OGR, which has an updating function based on a binary Bayesian filter and inverse sensor model, and a time window with a specified observation length. Finally, the mass center of the grids with occupancy belief over the threshold is defined as the measurement result. A numerical simulation and experiments verified the proposed method is suitable for a quasi-static measurement with a given accuracy requirement, featuring dynamic performance and robustness.